2012
DOI: 10.1017/s1368980012005010
|View full text |Cite
|
Sign up to set email alerts
|

Associations of diet quality with dairy group membership, membership duration and non-membership for Kenyan farm women and children: a comparative study

Abstract: Objective: To examine associations among diet quality and dairy group membership, membership duration and non-member status for women and school-aged children in rural Kenya. Design: A cross-sectional survey, using chain referral sampling, was conducted and diet quality indices and prevalence of inadequate intake (PII) were estimated using the 'estimated average requirement' cut-off point method from single 24 h recalls, using a Kenyan nutrient database. PII was compared among members and non-members and among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Approximately 40% of Kenyan women experience vitamin A deficiency [30] and our previous research that found a high proportion of the study group had inadequate vitamin A intake [16]. Independent of dairy group membership, the positive effects on DGLV and OF consumption and vitamin A intake may be explained by a displacement of 'other fruit and vegetables' in response to intervention messages.…”
Section: Vitamin a Intakementioning
confidence: 92%
See 4 more Smart Citations
“…Approximately 40% of Kenyan women experience vitamin A deficiency [30] and our previous research that found a high proportion of the study group had inadequate vitamin A intake [16]. Independent of dairy group membership, the positive effects on DGLV and OF consumption and vitamin A intake may be explained by a displacement of 'other fruit and vegetables' in response to intervention messages.…”
Section: Vitamin a Intakementioning
confidence: 92%
“…Stemming from these efforts, significant improvements in dairy animal feeding, reproduction, mastitis control, [14] and milk production were reported [15]. As well, WDL members had higher dairy income, greater household food security, consumed more milk, and had better quality homes, water access and social support compared to non-members [16]. However, average dietary diversity (DD) was low (less than five) for member and non-member women.…”
Section: Wakulima Dairy Ltd (Wdl) Is Located Within the Mukurwe-ini mentioning
confidence: 99%
See 3 more Smart Citations